PERBURUAN SATWA YANG DILINDUNGI DI HUTAN ADAT DATUK BENDAHARA SAKTI KUBANG BUAYA KECAMATAN ROKAN IV KOTO - Bulkhaini,; Munir , Abdul (Sisi Lain Realita, 2024)
Rokan Hulu Regency is a rich region in biodiversity. Rokan Hulu is an area that has a long list of protected wild animals that are threatened with extinction. Protected Wild Animals Protected Wilds are all animals that live on land, water and/or air that still have protected wild characteristics, both free living and those kept by humans. The extinction of protected wildlife is caused by the reduction and destruction of habitat as well as the hunting and trade of illegal animals that are traded in the Black Market. The purpose of this study was to find out what are the factors behind the hunting of protected wild animals, especially in Cipang Kanan Village, Rokan IV Koto. This study uses a phenomenological approach and uses qualitative descriptive research. The results of this study are the appropriate target factor, the motivated actor factor and also the lack of guarding factor which is the background of the rampant phenomenon of hunting for protected wild animals.